Running at the Devil with God's word. The pamphlets of the Early-Reformation preacher, Jacob Strauss - Smyth, Jennifer (Trinity College (Dublin, Ireland). Department of History, 2010)
This thesis examines the printed pamphlets of a preacher of the early German Reformation, Jacob Strauss. The analysis is based primarily on my translations from German of Strauss's pamphlets; manuscript evidence from the Thiiringisches Hauptstaatsarchiv in Weimar; and a variety of printed works by Strauss's contemporaries. Earlier, German-language works on Strauss have reconstructed biographical details and offered summaries and separate analyses of his printed works. This thesis investigates Strauss's objectives in adopting the 'new medium' of the pamphlet and in exploiting the 'old medium' of the sermon. The pamphlets are treated as an extension of Strauss's role as preacher insofar as they are considered to address the laity, broadly identified with the 'common people'. To identify Strauss's aims in addressing this group, his publications are treated thematically. They are particularly suited to such treatment as they were produced in a relatively brief period and cover numerous topics. The emphasis in the analysis is on Strauss's tools for persuasion in the cause of reform and thus on elements which can be used to work towards an analysis of his work as teacher, missionary, and propagandist.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin